Combination of slow deep breathing with rose aromatherapy and progressive muscle relaxation on blood pressure among hypertensive patients in Manado City - Faradilla Miftah Suranata; Rahmat Hidayat Djalil; Nelfa Fitria Takahepis; Bunga Pakaya (Science Midwifery, 2026)
Hypertension is one of the major health problems in Manado City, with an increasing prevalence and the potential to cause serious complications if left uncontrolled. Non-pharmacological interventions, such as the combination of slow deep breathing (SDB) with rose aromatherapy and progressive muscle relaxation (PMR), may serve as alternative therapies to support blood pressure management by increasing parasympathetic nervous system activity. This study aimed to evaluate the effectiveness of SDB combined with rose aromatherapy and PMR in reducing blood pressure among patients with hypertension. This study employed a quantitative pre-experimental design with a two-group pretest-posttest approach. A total of 32 patients with hypertension were allocated into two intervention groups: the SDB combined with rose aromatherapy group and the PMR group. Both interventions were conducted for four weeks. Systolic and diastolic blood pressure measurements were recorded before and after the interventions. The results showed that the SDB combined with rose aromatherapy group experienced a reduction in systolic blood pressure of 10 mmHg (p=0.001) and diastolic blood pressure of 5.43 mmHg (p=0.001). Meanwhile, the PMR group demonstrated a reduction in systolic blood pressure of 13.4 mmHg (p=0.001) and diastolic blood pressure of 5.3 mmHg (p=0.001). The Independent Samples T-Test revealed significant differences in post-intervention blood pressure between the two groups for both systolic blood pressure (mean difference=-18.33; 95% CI: -19.18 to -0.85; p=0.015) and diastolic blood pressure (mean difference=-9.02; 95% CI: -9.57 to -0.55; p=0.014). Conclusion: Both SDB combined with rose aromatherapy and PMR significantly reduced blood pressure among patients with hypertension. Slow Deep Breathing (SDB) combined with rose aromatherapy showed greater reductions in post-intervention systolic and diastolic blood pressure compared with Progressive Muscle Relaxation (PMR), supporting its potential role as a non-pharmacological approach for hypertension management.